Climate monitoring bulletin for the major river basins, Volume 3, Number 23 - Senna, Renato Cruz; Carvalho, Luan Rogério Rodrigues; Arcos, Adriano Nobre; Rocha, Tainá Sampaio Xavier Conchy (My University, 2025)
Analysis of the behavior of rainfall (accumulated in 30 days) over the main river basins in the Amazon with the categorization of positive and negative rainfall anomalies for the period, calculation of the average value of accumulated rainfall by river basin and analysis of behavior in relation to the available climatology, it also presents a descriptive graph of weekly behavior (accumulated over 7 days).